The Relationship Between Physical Activity and Dietary Patterns with Blood Sugar Control in Patients with Type 2 Diabetes Mellitus in Karawang Regency in 2025 - Tuti Susilawati; Bambang Setiaji; Endang Suryadi (Eduvest - Journal of Universal Studies, 2026)
Diabetes mellitus ranks as the third leading cause of death in Indonesia, accounting for 6.7% of all fatalities, with the country holding the seventh position globally in diabetes prevalence at 8.5%. In Asia, 16.2% of the population has type 2 diabetes mellitus, while Indonesia's prevalence reached 6.7% in 2020. The study's main objectives are to identify the most influential factors and examine the relationship between dietary patterns, physical activity, and blood sugar control. This observational analytic study with a cross-sectional design was conducted at three community health centers in Karawang Regency—Medangasem, Rengasdengklok, and Karawang—selected through random sampling and involving 111 patients with type 2 diabetes mellitus. Data were collected using validated questionnaires and analyzed using chi-square tests and multiple logistic regression. Results demonstrated significant associations between physical activity (p < 0.001), fat intake (p = 0.004), and carbohydrate intake (p = 0.015) with blood sugar control, while protein intake, vitamin C intake, and vitamin A intake showed no significant associations. Physical activity emerged as the most dominant factor influencing blood sugar control (p < 0.001, OR = 5.636, 95% CI: 2.230–14.245). These findings underscore the critical role of physical activity and dietary management in controlling blood glucose levels among patients with type 2 diabetes. It is recommended that individuals with type 2 diabetes pay closer attention to their dietary intake to align with nutritional guidelines, maintain controlled blood glucose levels, and engage in regular physical activity of at least 30 minutes daily.